Dyskurs strachu? Jak się nie bać współczesnych mediów - Radosław Rybkowski (Jesuit University Ignatianum in Krakow, 2011)
One of the main topics of the modern media coverage are: disasters, crimes, diseases, wars, and fear. The use of fear as an important vehicle for creating common perception of the world has been especially important after 9/11 terrorist attacks in the United States. The fear of another attack has defined American patriotism and has been an important driving force in launching Second Gulf War. US documentary series "Carrier", directed by Maro Chermayeff, is a perfect example of the use of fear in defining common goals and perception of the war effort of the Americans. David Altheide's works provides an extra insight into the nature of modern media and the way they use fear to achieve their own goals (including sales increase). His concept of the "discourse of fear", applied to the "Carrier", can help to understand mass media news without fear.